Effects of Intermittent Drought During Tillering and Stalk Elongation Stages on the Physiological Attributes of Diverse Sugarcane Genotypes - Mintra Tippa-art; Peeraya Klomsa-ard; Patcharin Songsri; Nakorn Jongrungklang (Stresses)
The growth and yield of sugarcane have been negatively impacted by drought stress, particularly during two stages of development, namely, tillering and elongation. This research aimed to determine the responses of diverse sugarcane cultivars under water-withholding conditions during the tillering and stalk elongation stages. A factorial experiment in CRD with four replications was used. Two water regimes were allocated to factor A, namely, providing water and controlling soil moisture at the field capacity (FC), and providing water-withholding (WW) conditions continuously at the tillering and elongation stages. Five different sugarcane cultivars were assigned to factor B. Drought significantly impacts the physiological characteristics of sugarcane during both the tillering and stalk elongation stages, with the tillering stage being more severely affected. KK3 and PK4 demonstrated superior drought tolerance in terms of relative water content and stomatal conductance, maintaining higher levels compared to the others. Increased proline content in the roots of K88-92 and MPT14-618 under drought conditions facilitated osmotic adjustment. Biomass production varied significantly across genotypes, with MPT14-618, KK3, and K88-92 maintaining better biomass compared to UT12 and PK4. The findings suggest that drought stress differentially impacts sugarcane genotypes, with KK3, K88-92, and MPT14-618 exhibiting superior physiological and growth resistance. These genotypes show promising potential for cultivation in arid regions.